Quality of greywater from a city district before and after treatment in a green wall - Sami, Mashreki; Hedström, Annelie; Kvarnström, Elisabeth; Herrmann, Inga (Luleå University of Technology, 2023)
The dataset presented here consists of raw data on the quality of influent greywater generated from a city district with 800 PE (population equivalent) and the effluent quality of greywater after treatment using a green wall. Five natural filter materials (pumice, biochar, hemp fiber, spent coffee ground, and composted fiber soil) were used in the green wall and tested for three hydraulic loading rates (54, 108 and 216 l/m2/d). The influent and effluent samples were taken manually between November 2021 and March 2022 and were analyzed for organic material, nutrients, pathogens, anionic surfactants, salt and microplastics. Supporting parameters e.g. suspended solids and pH, are also included in the dataset. Further, for microplastics, results from blank samples are included. This dataset was used to evaluate the treatment efficiency of the filter materials at different hydraulic loading rates.

1. Study_Description: This file includes the summary of the research study, data collection and the standard analytical methods used for analyzing different parameters.
2. greywater_quality: The influent and effluent concentrations of all parameters analyzed during all sampling events.

Datauppsättningen som presenteras här består av rådata med avseende på kvaliteten på inkommande bad-, disk- och tvättvatten (BDT-vatten), som genereras från en stadsdel med 800 PE (population equivalent), och kvaliteten på BDT-vattnet efter rening i en grön vägg. Fem naturliga filtermaterial (pimpsten, biokol, hampafiber, kaffesump och komposterad fibermull) användes i den gröna väggen och testades för tre hydrauliska belastningshastigheter (54, 108 och 216 l/m2/d). Inflödesproverna och proverna efter behandling i den gröna väggen togs manuellt mellan november 2021 och mars 2022. De analyserades med avseende på innehåll av organiskt material, näringsämnen, patogener, anjoniska tensider, salt och mikroplaster. Stödparametrar, t.ex. suspenderade fasta partiklar och pH, ingår också i datasetet. Vidare, för mikroplaster, ingår resultat från blankprover. Denna datauppsättning användes för att utvärdera behandlingseffektiviteten hos de olika filtermaterialen vid olika hydrauliska belastningshastigheter.

1. Study_Description: Detta dokument innehåller en sammanfattning av hur provtagningar och analyser utfördes.
2. greywater_quality: Uppmätta koncentrationer i inkommande och utgående vatten vid de olika provtagningstillfällena.
Kvalitet på bad-, disk- och tvättvatten (BDT-vatten) från en stadsdel: inkommande och efter behandling i en grön vägg
Keywords: water quality; vattenkvalitet; phosphorus; fosfor; micro-litter; mikroskräp; biochar; biokol; nitrogen; kväve; pathogens; patogener; greywater; gråvatten; surfactants; microplastics; mikroplaster; surfactants; tensider; gråvatten; graywater; Environmental Engineering; Naturresursteknik; Environmental Management; Miljöteknik och miljöledning; Water Treatment; Vattenbehandlingsbioteknik